The Role of Agile Leadership: Enhancing School Innovation and Adaptability The Role of Agile Leadership: Improving School Innovation and Adaptation - Edy Rakhmadi; Norliani Norliani; Muhammad Muhaimim; Aslamiah Aslamiah; Celia Cinantya (Green Publisher Indonesia, 2025)
In the era of rapid educational transformation, school leadership plays a crucial role in fostering innovation and adaptability. This study explores the role of Agile Leadership in driving learning innovation at SMAN 1 Kelumpang Hilir. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. Data analysis followed the Miles and Huberman model, consisting of data condensation, data display, and conclusion drawing to ensure comprehensive findings. The results indicate that implementing adaptive, collaborative, and flexible Agile Leadership fosters an innovative learning environment. School leaders who adopt these principles enhance teacher and student engagement in project-based learning and digital technology integration. Key aspects of Agile Leadership include decision-making flexibility, stakeholder collaboration, and curriculum innovation. Additionally, Agile Leadership promotes continuous feedback and data-driven decision-making, enabling schools to swiftly adapt to policy changes and student needs. This study provides practical insights for school leaders to integrate Agile Leadership into educational management, ensuring adaptability and sustainability in a dynamic learning environment.